Incidental Emotions and Cooperation in a Public Goods Game - Nguyen, Yen; Noussair, Charles N. (Frontiers in Psychology, 2022)
The study reported here considers the relationship between emotional state and cooperation. An experiment is conducted in which the emotions of fear, happiness, and disgust are induced using 360-degree videos shown in virtual reality. There is also a control condition in which a neutral state is induced. Under the Fear, Happiness, and Disgust conditions, the cooperation level is lower than under the Neutral condition. Furthermore, cooperation declines over time in the three emotion conditions, while it does not under Neutral. The findings suggest that emotions are associated with the dynamic of declining cooperation.